CALLUS INDUCTION OF COTTONI SEAWEED (Kappaphycus alvarezii (Doty) Doty) COLLECTED FROM NATUNA ISLANDS, RIAU ISLANDS PROVINCE - Erina Sulistiani (SEAMEO BIOTROP, 2012)
The objective of this study was to obtain the optimal medium for callus induction from thallus explants off Kappaphycus alvarezii (Doty) and to regenerate filamentous callus from induced callus. Before cultured cottonii seaweeds collected from the Natuna Islands (Riau Islands Province) were acclimatized in greenhouse and in semi-sterile culture in the laboratory. Sterilized explants were cultured on PES and Conwy media solidified with 0.8% Bacto Agar. In each of these media two combinations of plant growth regulators i.e. BA+IAA and BA+NAA were added. The concentrations of BA used were 0, 0.5, 1 mg/l, the concentrations of IAA were 0, 2.5, 5 mg/l, whereas the concentration of NAA were 0, 0.5, 1 mg/l. The result indicated that the optimal medium for callus induction was PES solidified medium supplemented with BA 1 mg/l. Types of callus formed were (a) white compact callus, (b) white filamentous callus, (c) greenish/brownish callus. Regeneration of callus into clumps offilament had been done by subculturing the callus into PES solidified medium supplemented with BA 1 mg/l + IAA 2.5 mg/l